Political affiliation or need for cognition? It depends on the post: Comparing key factors related to detecting health disinformation in the U.S. - Joey F. George (PLoS ONE, 2025)
We investigate why people believe disinformation about health-related issues. Acting on disinformation could lead to severe injuries and even death. Five hundred eight American respondents each reviewed 10 different social media posts about health-related topics, and 60% of the posts contained disinformation. They were asked to evaluate the posts for their honesty and explain their decisions. Respondents successfully detected disinformation about 2/3 of the time. Across all participant responses, need for cognition was the only factor important to successful detection of disinformation. When investigating each social media post individually, need for cognition was key for 35% of the posts, while political affiliation was key for 15%. Neither factor was important for the remaining 50% of posts. People with a high need for cognition were adept at detecting online disinformation, but those with conservative political affiliations were not. Those best suited to detecting health-related disinformation either had a high need for cognition or a liberal political affiliation.